AN APPROACH TO ENGLISH CONVERSATION WITH IRAQI UNIVERSITY STUDENTS - M. Al-Sawaf (آداب الرافدين, 1974)
We maintain that the most difficult of the four skills involved in learning a foreign language are speaking and writing. The other two skills being listening and reading. The former couple of skills are active because they are productive, whereas the latter ones are passive as they are receptive or absorptive, and production is always more difficult than reception. (1) In speaking and writing, the learner has to put into operation the absorbed, or dormant, laguage units of vocabulary, structure, stress, rhythm and intonation in such a way as to achieve intelligibility. If this goal is not achieved, communication breaks down and the learning process is proved a failure. But in listening and reading, both silent and aural, the learner is exposed to bits of language, short or long, and the amount acquired depends wholly on the listener's, or reader's, mastery of the language. There is, therefore, no real production, no actual usage, involved in these tow skills.